Academics wellbeing in public universities, Nigeria: the role of transformational leadership, perceived stress, organizational justice and self-efficacy - Ahmed, Obobanyi Momohjimoh (2019)
The main purpose of this study was to examine the relationships among transformational leadership (TL), perceived stress (PS), organizational justice (OJ), self-efficacy (SE) and academics wellbeing in public universities, Nigeria (PUN). Precisely, this study aimed at investigating the effect of self-efficacy as a mediating variable in explaining the relationships among transformational leadership, perceived stress and organizational justice on academics wellbeing. The motivation for this research was driven by the increasing attention worldwide to employee wellbeing as a crucial factor for organizational effectiveness and efficiency. However, research for improving this vital element of organizational management still remain limited in literature. Accordingly, this study drawn upon both job demands-resources theory and Adams equity theory to assess and position the possible relationships between the variables in the research framework. In accomplishing this objective, a cross-sectional survey design and cluster sampling technique were used. A total of 293 faculty staff of public universities located in the North-West geopolitical zone of Nigeria participated in the study. A Partial Least Squares-Structural Equation Modelling (PLS-SEM) technique was used to test the postulated hypotheses. Findings from analyses supported the hypothesized direct effect of TL on academics wellbeing; and direct effect of PS on academics wellbeing. In addition, self-efficacy mediated the relationships between TL and academics wellbeing; and the relationship between PS and academics wellbeing. Therefore, to foster an optimally academics wellbeing in public universities in Nigeria, the management of the institutions should focus on the enhancement of self-efficacy of faculty staff. In other words, self-efficacy serves a strong mechanism through which TL and PS positively influences academics wellbeing in public universities, Nigeria. Finally, theoretical and practical implications as well as future research direction are discussed.